Problem of impulsive regulator for one dynamical system of the Sobolev type - Vlasenko, L. A.; Rutkas, A. G.; Samoilenko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2008)
We establish conditions for the existence of an optimal impulsive control for an implicit operator differential equation with quadratic cost functional. The results obtained are applied to the filtration problem.